E$_{alpha } $-Ulam-Hyers Stability Result for $psi $-Hilfer Nonlocal Fractional Differential Equation - Almalahi, Mohammed A.; Panchal, Satish K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we study the existence and uniqueness results of }$ψ ${ -Hilfer nonlocal fractional differential equation with constant coefficient by using some properties of Mittag-Leffler function and fixed point theorems such as Banach and Schaefer's fixed point theorems. The generalized Gronwall inequality lemma is used in analyze E}$_{α }${ -Ulam-Hyers stability. Finally, an example is provided to illustrate the obtained results.